2010
DOI: 10.1063/1.3505046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic ions on DNA damage induced by 1 eV to 60 keV electrons

Abstract: We report the results of a study on the influence of organic salts on the induction of single strand breaks (SSBs) and double strand breaks (DSBs) in DNA by electrons of 1 eV to 60 keV. Plasmid DNA films are prepared with two different concentrations of organic salts, by varying the amount of the TE buffer (Tris-HCl and EDTA) in the films with ratio of 1:1 and 6:1 Tris ions to DNA nucleotide. The films are bombarded with electrons of 1, 10, 100, and 60 000 eV under vacuum. The damage to the 3197 base-pair plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 53 publications
(94 reference statements)
1
18
0
Order By: Relevance
“…This small increase suggests that although the CS for the sum of the ionization and fragmentation channels at 100 eV is reported to be larger by one or two orders of magnitude than that at 10 eV for most organic molecules [74][75][76], resonant and nonresonant mechanisms have relatively similar contributions to the generation of DNA SBs at both energies. Similar comparisons were also made in previous studies (i.e., the yields for the formation of single and double SBs by 10 and 100 eV electrons had comparable values) [73,77,78]. Therefore, our results confirm the previous suggestion that for a given CS value, the formation of transient anions and DEA are much more efficient processes than others to induce SBs in DNA.…”
Section: B Correction Factorsupporting
confidence: 81%
“…This small increase suggests that although the CS for the sum of the ionization and fragmentation channels at 100 eV is reported to be larger by one or two orders of magnitude than that at 10 eV for most organic molecules [74][75][76], resonant and nonresonant mechanisms have relatively similar contributions to the generation of DNA SBs at both energies. Similar comparisons were also made in previous studies (i.e., the yields for the formation of single and double SBs by 10 and 100 eV electrons had comparable values) [73,77,78]. Therefore, our results confirm the previous suggestion that for a given CS value, the formation of transient anions and DEA are much more efficient processes than others to induce SBs in DNA.…”
Section: B Correction Factorsupporting
confidence: 81%
“…More recently, Dumont et al 23 and Zheng and Sanche 24 observed a protective effect on DNA damage by organic salts, particularly in the chemical buffer used in most of the experiments involving DNA (Tris-HCl, EDTA). Single and double strand breaks (SSB and DSB) were considerably reduced in plasmid DNA under irradiation with 1 eV to 60 keV electrons.…”
Section: Introductionmentioning
confidence: 99%
“…27 After lyophylization, the films were transferred directly to the UHV chamber of the LEE irradiator. The DNA films were then bombarded with an incident electron beam of 6 nA and electron energy of 10 ± 0.5 eV, during exposures of 5 to 60 s. The time-response of the yields was expressed in term of the fluence (i.e., the total number of electrons hitting the target).…”
Section: Methodsmentioning
confidence: 99%